Kocuria kristinae-caused sepsis in an infant with congenital tufting enteropathy - Malik Aydin; Rainer Ganschow; Martin Jankofsky (The Turkish Journal of Pediatrics)
Congenital tufting enteropathy (CTE) is characterized by the early-onset of chronic diarrhea and the inability to develop. It is a rare congenital disease with a low prevalence of 1:50,000 - 100,000 live births p.a. The histopathology is characterized by villous atrophy and the characteristic epithelial tufts. Recent identification of causative mutations in EpCAM has enhanced our understanding of this disease. Due to its severe clinical course, patients are dependent on parenteral nutrition to thrive successfully. Catheter-associated blood stream infections have become the primary problem for pediatric patients. Infections with Kocuria kristinae are rare. This report is about a 3-month-old girl with CTE suffering from a central venous catheter related mono-sepsis by K. kristinae. A sepsis therapy with meropenem and vancomycin improved her general state rapidly. Only few cases in the literature with CTE and K. kristinae are described. To the best of our knowledge, this is the first report presenting two coincidences in one case.